Intelligent Electric Power Systems with Active-Adaptive Electric Networks: Challenges for Simulation Tools - Ufa Ruslan A.; Sulaymanova Venera A.; Borovikov Yuri S. (MATEC Web of Conferences, 2015)
The motivation of the presented research is based on the needs for development of new methods and tools for adequate simulation of intelligent electric power systems with active-adaptive electric networks (IES) including Flexible Alternating Current Transmission System (FACTS) devices. The key requirements for the simulation were formed. The presented analysis of simulation results of IES confirms the need to use a hybrid modelling approach.